2022
DOI: 10.1111/eci.13794
|View full text |Cite
|
Sign up to set email alerts
|

Circulating suPAR associates with severity and in‐hospital progression of COVID‐19

Abstract: Background COVID‐19 disease progression is characterized by hyperinflammation and risk stratification may aid in early aggressive treatment and advanced planning. The aim of this study was to assess whether suPAR and other markers measured at hospital admission can predict the severity of COVID‐19. Methods The primary outcome measure in this international, multi‐centre, prospective, observational study with adult patients hospitalized primarily for COVID‐19 was the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…27 were selected for full text review, as displayed in the flowchart in Figure 2. Finally, 15 studies were included in this meta-analysis [10,[15][16][17][22][23][24][25][26][27][28][29][30][31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 were selected for full text review, as displayed in the flowchart in Figure 2. Finally, 15 studies were included in this meta-analysis [10,[15][16][17][22][23][24][25][26][27][28][29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…During the pandemic, the predictive ability of suPAR as a biomarker of illness severity and mortality gained attention. SuPAR levels at admission in patients who survived hospitalization for COVID-19 were lower than in those who died (5.8 ng/mL vs. 8.2 ng/mL, respectively, p<0.001) [15]. SuPAR levels also differed based on disease outcomes: severe cases had significantly higher suPAR levels than mild cases (3.87 ng/mL vs. 2.84 ng/mL, respectively; p=0.01), whereas patients with mild COVID-19 had elevated suPAR levels compared to healthy subjects (2.84 ng/mL vs. 1.68 ng/mL, respectively; p=0.02) [16].…”
Section: Introduction and Objectivementioning
confidence: 86%
“…If the tests are adopted for routine use, cut-offs associated with particular clinical management decisions (for example, admission or discharge from the emergency department) or weightings within multivariable triage tools (prediction models) should be assay-dependent. 11,12,22 Similarly, if suPAR measurements are used to inform participant recruitment into clinical trials, it is important that eligibility criteria are tailored to the assay used for enrolment. 23…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Recently, our group and others developed clinical prediction models incorporating suPAR for both community- and hospital-based triage of patients with Covid-19. 11,12 However, although suPAR is measurable using a commercially-available rapid test, these studies quantified suPAR using laboratory-based immunoassays.…”
Section: Introductionmentioning
confidence: 99%
“…Biomarkers are recognized as essential tools for the diagnosis and management of all the above-mentioned respiratory diseases. It has been previously suggested that suPAR, the soluble form of urokinase plasminogen activator receptor (uPAR), which is a glycosyl-phosphatidylinositol (GPI)-linked membrane protein, can be used as a marker of both inflammation and disease severity [ 21 ]. A recent study that investigated the effectiveness of suPAR as an indicator of the severity of asthma, a chronic inflammatory disease of the airways, demonstrated that suPAR levels could discriminate moderate uncontrolled asthma from severe asthma [ 22 ].…”
mentioning
confidence: 99%